Accuracy of Reduction Depths of Tooth Preparation for Porcelain Laminate Veneers Assisted by Different Tooth Preparation Guides: An In Vitro Study. Issue 7 (15th December 2021) - Gao, Jing; He, Jinxiu; Fan, Lin; Lu, Jiayi; Xie, Chenyang; Yu, Haiyang
Abstract: Purpose: To evaluate the accuracy (trueness and precision) of reduction depths of guided veneer preparation assisted by four tooth preparation guides. Materials and Methods: Fifty resin artificial teeth were randomly divided into five groups (n = 10): a freehand group (F), silicone guide group (S), thermoplastic guide group (T), 3D printed uniform guide group (D), and 3D printed auto‐stop guide group (A). A preparation for a window veneer on the maxillary right central incisor was performed by two surgeons who used tooth preparation guides for assistance. The maxillary right central incisors were scanned before and after the preparation. The reduction depths were measured in the cervical, middle, and incisal thirds of the prepared surface, and depth maps were created using Geomagic Control X software. The accuracy of the reduction depths at each third was evaluated using both trueness and precision values. The trueness of the reduction depths was determined by calculating the mean absolute differences (MADs) compared to the planning depth, and precision was determined by the standard deviation (SD). The collected data were statistically analyzed using one‐way ANOVA and the least significant difference test (α = 0.05). Results: The MAD ± SD values of the reduction depths in the cervical‐third region in groups F, S, T, D, and A were 0.19 ± 0.04, 0.12 ± 0.03, 0.09 ± 0.02, 0.07 ± 0.02, and 0.05 ± 0.01 mm, respectively. In the middle‐third region, the MAD ± SD values of groups F–A were 0.19 ± 0.05, 0.13 ± 0.02, 0.09 ± 0.01, 0.06 ± 0.01, and 0.05 ± 0.01 mm. In the incisal‐third region, the MAD ± SD values were 0.27 ± 0.05, 0.16 ± 0.04, 0.11 ± 0.03, 0.07 ± 0.01, and 0.05 ± 0.01 mm, respectively. Significant differences in trueness and precision values were found across different groups (F = 45.378, p = 0.000), where group F showed higher MADs than the other 4 groups ( p = 0.000), and the highest MADs were detected in group S among the 4 groups in all regions ( p = 0.000). Group T showed significantly higher MADs than groups D (P = 0.008) and A ( p = 0.001), except in the cervical‐third region, where no significant difference was observed between groups T and D ( p = 0.077). There was no significant difference between groups D and A ( p = 0.148). The deviation map showed significant differences among groups (F = 15.963, p = 0.000), group T presented less deviation than group F ( p = 0.000) and group S ( p = 0.027) and showed more deviation than group A ( p = 0.007). Conclusion: Tooth preparation guides provided more accuracy for veneer preparation than freehand preparation. Among the 4 guides, the 3D printed auto‐stop guide presented the lowest absolute difference (0.05 mm) and the silicone guide showed the highest absolute difference of preparation (0.12–0.16 mm).